Simulação de inundações através do modelo HAND. Estudo de caso: zona urbana de Alegrete-RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Over the years, floods has been a notorious problem in the municipality of Alegrete, located in the western half of the state of Rio Grande do Sul, located close to half of the river basin course and allocated to the banks of the Ibirapuitã river. The urban area is often affected by flooding of the Ibirapauitã River and its tributaries, Arroio Jararaca, Arroio Regalado and Arroio Caverá, generating large floods. These are natural processes, inherent to river dynamics. Throughout human history, this process has positively and negatively influenced society. When this influence is negative, hydrological disasters occur. One of the most important preventive measures for hydrological disasters is the identification and mapping of susceptibility areas. It is in this context that the objective of this work, therefore, was to test the applicability of the Height Above the Nearest Drainage (HAND) model for the mapping of flood susceptible areas in the municipality of Alegrete. The model was used through the Brazilian methodology developed at INPE, through the TerraView software with a plug-in extension containing the hydrological tools, which normalizes the MDT at the nearest drainage level, thus generating simulations. just varying the fluviometric quota, producing flood maps of the municipality. Thus, the flood risk spatialization for the urban area was performed using digital terrain modeling with QGIS software. The quotas used were classified as: nonexistent risk, high risk and alert quota. To evaluate the used methodology , historical satellite images and area images were compared with the simulations developed in the software. Another way to evaluate was to compare affected neighborhoods based on historical surveys conducted on other projects. The results validate the HAND model as a useful tool for mapping flood-prone areas, especially where there is no hydrological monitoring.
Keywords: Engenharia civil; Inundações; Height Above the Nearest Drainage; Hidrologia; Civil engineering; Floods; Hydrology; CNPQ::ENGENHARIAS